How to promote cooperation in the hospitality industry: Generating practitioner-relevant knowledge using the GABEK qualitative research strategy - Pechlaner, Harald; Volgger, M. (2012)
Purpose: While it is possible to classify the previously suggested conditions to the promotion of interorganizational cooperation as either referring to strategic interdependence or to structural and procedural conditions, it is unclear which approach is more critical to the promotion of local and regional cooperation in the hospitality industry at the network level. Therefore, the purpose of this paper is twofold: to inductively develop propositions regarding the promotion of such cooperation in order to evaluate the relative importance of the two conflicting positions, and to demonstrate the suitability of GABEK to the development of these propositions. Design/methodology/approach: Following a qualitative case study design, data were gathered by conducting 15 open interviews in a South Tyrolean destination and analyzed with the aid of the GABEK technique. Findings: The results suggest that the structural and procedural conditions are relatively more critical to the promotion of interorganizational cooperation in the hospitality industry: first, the balancing of the efficiency and legitimacy dimensions via the organizational and procedural design of the cooperation seems crucial; second, intermediary organizations, if characterized by good corporate governance, may have a positive influence on cooperation; and third, the application of GABEK-like tools may facilitate the finding of commonly shared solutions in cooperative configurations. Practical implications: The research reveals actionable insights regarding the improvement of interfirm cooperation by offering managers tangible measures and a tool for implementing the theoretical concepts. Originality/value: The paper is original because it contributes to evaluating the two main approaches to the promotion of cooperation and because it proposes an innovative methodology (GABEK) for practice-oriented qualitative research. © Emerald Group Publishing Limited.